The Short-Rooted Phenotype of the brevis radix Mutant Partly Reflects Root Abscisic Acid Hypersensitivity - Rodrigues, Americo (American Society of Plant Biologists, 2009)
To gain further insight into abscisic acid (ABA) signaling and its role in growth regulation, we have screened for Arabidopsis (Arabidopsis thaliana) mutants hypersensitive to ABA-mediated root growth inhibition. As a result, we have identified a loss-of-function allele of BREVIS RADIX (BRX) in the Columbia background, named brx-2, which shows enhanced response to ABA-mediated inhibition of root growth. BRX encodes a key regulator of cell proliferation and elongation in the root, which has been implicated in the brassinosteroid (BR) pathway as well as in the regulation of auxin-responsive gene expression. Mutants affected in BR signaling that are not impaired in root growth, such as bes1-D, bzr1-D, and bsu1-D, also showed enhanced sensitivity to ABA-mediated inhibition of root growth. Triple loss-of-function mutants affected in PP2Cs, which act as negative regulators of ABA signaling, showed impaired root growth in the absence of exogenous ABA, indicating that disturbed regulation of ABA sensitivity impairs root growth. In agreement with this result, diminishing ABA sensitivity of brx-2 by crossing it with a 35S:HAB1 ABA-insensitive line allowed significantly higher recovery of root growth after brassinolide treatment. Finally, transcriptomic analysis revealed that ABA treatment negatively affects auxin signaling in wild-type and brx-2 roots and that ABA response is globally altered in brx-2. Taken together, our results reveal an interaction between BRs, auxin, and ABA in the control of root growth and indicate that altered sensitivity to ABA is partly responsible for the brx short-root phenotype.